THE INFLUENCE OF SOCIAL COMPANION COMPETENCE ON THE EFFECTIVENESS OF PKH SOCIAL ASSISTANCE UTILIZATION BY KPM - Abdul Rojak; Agus Sahyono (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study aims to analyze the influence of social assistant competency on the effectiveness of the utilization of social assistance funds from the Family Hope Program (PKH) by Beneficiary Families (KPM) in Sukawali Village, Pakuhaji District. The competency dimensions analyzed include knowledge, skills, and attitudes in carrying out assistance tasks. Methods: This study uses a quantitative approach with survey techniques and simple linear regression analysis of 50 randomly selected KPM. Results: The results showed that social assistant competency had a positive and significant effect on the effectiveness of PKH fund utilization (regression coefficient = 0.493; p <0.001). The regression model has met the assumptions of linearity and homoscedasticity. These findings underline the importance of competency-based training to improve the role of social assistants in encouraging the use of funds that are targeted and sustainable funds. Keyword: Competence, Social Companion, Social  Assistance Fund, Effectiveness